Optimization of Angkot Route Control System Based on - Suryani Prasetiyowati, Sri; Imrona, Mahmud; Sibaroni, Yuliant (International Journal of Engineering and Technology, 2019)
Traffic congestion problems is not only problem for big cities but already leading to small towns. It is necessary to provide an application that can help make an assessment quickly, accurately and cheap cost. Such studies can be used to specify a public policy issues related to traffic management. One of transportation mode cause congestion problem of urban areas of Indonesia is angkot. One of the problems that arise in transportation is not optimal route. In Indonesia, angkot is a unique public transportation. The problem relating to transport public transportation is related to improper route and passenger capacity are inadequate. Thus, in this study will establish a control system based on the route of public transportation passengersâ€™ optimum capacity. Completion of the issues discussed can be divided into two parts: the first relates to research in the field of prediction system for route weights based on the capacity of passengers in crowded places and the second relates to research in the field of the routing algorithm problem. The results obtained from this study was to perform route optimization breaking at the point route crowd. The test results showed that our system can give new optimal route for all sample routes.Â  These results can also be used to make new route of public transportation in the city of Bandung.Â